Aseptic meningitis caused by Leptospira spp diagnosed by polymerase chain reaction - Eliete Caló Romero; Roberta Morozetti Blanco; Paulo Hideki Yasuda (Memorias do Instituto Oswaldo Cruz, 2010)
Leptospirosis is a zoonotic disease caused by the pathogenic Leptospira spp. The clinical presentations are diverse, ranging from undifferentiated fever to fulminant disease including meningeal forms. The neurological leptospirosis forms are usually neglected. The aim of this study was to investigate leptospirosis as the cause of aseptic meningitis using different diagnostic techniques including the polymerase chain reaction (PCR). Thirty-nine cerebrospinal fluid (CSF) samples from patients presenting with meningeal abnormalities, predominance of lymphocytes and negative results by traditional microbiological tests were processed by leptospiral culture, anti-leptospiral antibody response and PCR. Leptospira spp DNA was detected in 23 (58.97%) of the CSF samples. Anti-leptospiral antibodies were found in 13 (33.33%) CSF samples. Twelve CSF samples were positive by PCR assay and negative by microscopic agglutination test (MAT) assay. Two CSF samples were positive by MAT and negative by PCR. The positive and negative agreement between both tests was 11 and 14, respectively. CSF samples from six cases of unknown diagnosis were positive by PCR assay. Eight cases showed positive results using PCR and MAT. Leptospirosis could be detected by PCR assay from the 3rd-26th day after illness onset. The sensitivity of the PCR was assessed with confirmed cases of leptospirosis (by MAT) and found to be 89.5%. All CSFs were negative by culture. PCR was found to be a powerful tool for diagnosing meningitis cases of leptospirosis. We recommend that it may be used as a supplementary diagnostic tool, especially in the early stages of the disease, when other diagnostic techniques such as serology are not sensitive.